Spatial Distribution and Regional Difference of Environmental Efficiency Based on Carbon Reduction Goals: Evidence From China - Pan, Wenyan; Gulzar, Muhammad Awais; Wang, Zongjun; Guo, Chensi (Frontiers in Environmental Science, 2022)
China will strive to achieve carbon peak by 2030 and carbon neutralization by 2060 cooperating with the system dominated by carbon intensity control and supplemented by total carbon emission control. This paper analyzes the environmental efficiency index of China, the empirical results show that the average growth rate is 4.5% from 2006 to 2017. A further decomposition of changes on scale efficiency and pure technical efficiency indicates that the pure technical efficiency maintains a long-term growth, and scale efficiency shows a fluctuant tendency. Above-mentioned changes show that various methods in China such as industrial structure adjustment and promotion of the development of high and new technologies have obtained the certain effect. From the perspectives of regional differences, the average changes of environmental efficiency in eastern, central and western regions as well as most of provinces and cities are all on the increase. On the space layout, a trend has been presented that the average changes in central regions exceed that in eastern regions. While the average changes in western regions are comparatively lower than eastern regions.